The abundance and diversity of butterflies (Lepidoptera: Rhopalocera) in Talaud Islands, North Sulawesi, Indonesia - Roni Koneri; MEIS J. NANGOY; PARLUHUTAN SIAHAAN (Society for Indonesian Biodiversity, 2019)
Abstract. Koneri R, Nangoy MJ, Siahaan P. 2019. The abundance and diversity of butterflies (Lepidoptera: Rhopalocera) in Talaud Islands, North Sulawesi, Indonesia. Biodiversitas 20: 3275-3283. Butterflies play a number of roles in the ecosystem. They help pollination and natural propagation and also are an important element of the food chain as prey for bats, birds, and other insectivorous animals. This study aimed to analyze the abundance and diversity of butterflies (Lepidoptera: Rhopalocera) in the Talaud Islands of North Sulawesi, Indonesia. The sampling method used was scan sampling along the transect line in three habitat types, namely, forest edge, farmland, and shrubland. The species diversity was determined by using the diversity index (Shanon-Wiener), the species richness index was calculated using the Margalef species richness index (R1), while species evenness was counted by using the Shannon evenness index (E). One-way ANOVA and Duncan test at the 95% significance level were used to determine differences in species richness, species abundance, species diversity values, and species evenness among habitat. In this study, we identified 1008 individuals of butterfly consisted of 32 species and five families. Nymphalidae was the dominant family with 15 species, while the highest abundance species was Eurema tominia. The highest species abundance, species richness index, species diversity index, and species evenness index were found in forest edge habitat. The largest similarity index of the composition of the butterfly communities was found in forest edge and farmland habitats. The abundance and diversity of butterfly species in a habitat are strongly influenced by the diversity of vegetation as shelter and source of nectar for butterflies, and the existence of a river as a source of water and minerals from wet rocks, mud, and sand along the riverside.